Respuesta :

We can equate both the functions to evaluate value of x and that will be the solution of [tex]f(x) = g(x)[/tex].

The solution is given as: [tex]x = 1[/tex]

Given that:

  • [tex]f(x) = 2x+ 1[/tex]
  • [tex]g(x) = -x + 4[/tex]

To find:

Solution of the equation [tex]f(x) = g(x)[/tex]

Substituting values of f(x) and g(x) in given equation:

[tex]f(x) = g(x)\\2x + 1 = -x + 4\\\\\text{Adding x on both the sides}\\2x + x + 1 = -x + x + 4\\3x + 1 = 4\\\\\text{Subtracting 1 from both the sides}\\3x + 1 - 1 = 4 - 1\\3x = 3\\\\\text{Dividing both the sides by 3}\\\dfrac{3x}{3} = \dfrac{3}{3}\\\\x = 1[/tex]

Thus, the solution of given equation is given as [tex]x = 1[/tex].

Learn more about solution of linear equations here:

https://brainly.com/question/10439298